Skeletal Muscle Calcium Channel Mutation R528G: Enhanced Channel Inactivation and Omega-Current at Hyperpolarization Contribute to Hypokalemic Periodic Paralysis. - Bednarz, Marcin; Da, Yuwei; Lehmann-Horn, Frank; Fan, Chunxiang; Schallner, Jens; Jurkat-Rott, Karin (Journal of Neurological Research And Therapy, 2016)
Autosomal dominant inherited hypokalemic periodic paralysis (HypoPP) is caused by S4 voltage sensor mutations in skeletal muscle CaV1.1 calcium or NaV1.4 sodium channels. In the present study, a small German family with the known CaV1.1-R528G is described. The phenotype consists of short and infrequent episodes of limb weakness with ictal respiratory and cardiac involvement. There is incomplete penetrance in women, and acetazolamide is beneficial in two patients also taking daily potassium. Expression of the mutation in the GLT mouse muscle cell line revealed accelerated kinetics of inactivation by twofold, a left-shift of the steady-state inactivation curve by 13mV and a reduced recovery from fast inactivation by up to 39%. These changes suggest a stabilization of the inactivated state. Additional significant slowing of activation may support a second open state with differing ion selectivity or decreased activation of calcium-activated potassium channels and thereby contribute to weakness similar to other CaV1.1 mutations. Also, as documented for other HypoPP mutants, we found a hyperpolarization-induced inward guanidinium current of 22nS/nF which can be interpreted as an omega current along the voltage sensor gating pore that leads to a gain- of- function at potentials near the resting membrane potential. This finding can explain the long-lasting depolarizations that are known to lead to paralysis. The omega current is large enough so that a relatively mild hypokalemic trigger of 2.4mM already produces episodes of weakness in vivo.
Keywords: Skeletal Muscle Calcium Channel; CaV1.1; Hypokalemic Periodic Paralysis; CACNA1S; R528G Mutation; Omega Current; Channel Inactivation